ASPEK PENDUKUNG PERKEMBANGAN PESERTA DIDIK DAN IMPLIKASINYA DALAM PROSES PEMBELAJARAN - Nafisah Nurfaidah; Ali Maulida; Samsuddin (As-Sulthan Journal of Education, 2025)
This article aims to analyze the supporting factors that influence student development, such as learning motivation, aggression control, and the application of learning theories. This study uses a qualitative method with a literature review approach to analyze various relevant references. The research findings indicate that high learning motivation can improve students' academic performance, while proper aggression management can enhance social and emotional interactions. The application of constructivism theory and multiple intelligences in learning provides space for the development of various aspects of student intelligence. In conclusion, a holistic learning approach, considering both internal and external factors, can optimize the overall development of students.